2016
DOI: 10.1080/01616412.2016.1250857
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the miRNA–mRNA regulatory network in multiple sclerosis

Abstract: hsa-miR-30a, hsa-miR-93, hsa-miR-20b, and hsa-miR-20a might be the key participant in the pathophysiology of MS involved in signaling pathways including ribosome, tuberculosis, and pathways in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 42 publications
0
35
0
1
Order By: Relevance
“…There was a report showed that miR-20a-5p could be used as biomarker in the treatment response of naive patients with relapsing remitting MS with interferon-β (IFN-β) 17. These findings also suggested that miR-20a-5p might be an important player in the pathophysiology of MS 18. Since the role of miR-20a-5p in uveitis is not completely clarified, we determined to investigate the expression pattern and role of this molecule in VKH disease.…”
Section: Introductionmentioning
confidence: 97%
“…There was a report showed that miR-20a-5p could be used as biomarker in the treatment response of naive patients with relapsing remitting MS with interferon-β (IFN-β) 17. These findings also suggested that miR-20a-5p might be an important player in the pathophysiology of MS 18. Since the role of miR-20a-5p in uveitis is not completely clarified, we determined to investigate the expression pattern and role of this molecule in VKH disease.…”
Section: Introductionmentioning
confidence: 97%
“…MS is thought to result from a complex interplay of genetic, epigenetic, and environmental risk factors . MicroRNAs (miRNAs) are epigenetic factors that have been investigated in MS, and over 170 miRNAs have been found to be differentially expressed in various tissues in either adult‐onset MS or experimental autoimmune encephalomyelitis (EAE) in mice . One study specifically compared miRNA expression levels in ped‐MS cases to pediatric controls, and 12 upregulated and one downregulated miRNA were reported .…”
Section: Introductionmentioning
confidence: 99%
“…To conceptually analyze and intuitively visualize interactions in such a vast regulatory network, the construction of a molecular interaction map is the first step in modern biological studies 19,20 . A number of comprehensive regulatory maps have been constructed to help in the understanding of the mechanisms underlying complex biological systems [21][22][23][24] , however, only a handful of attempts have been made so far to develop a mechanistic understanding of complex inflammatory disorders through the investigation of underlying molecular interaction maps [25][26][27][28] .…”
Section: Problem and Research Gapmentioning
confidence: 99%